Novel perspectives of target-binding by the evolutionarily conserved PP4 phosphatase. Issue 12 (23rd December 2020) - Karman, Zoltan; Rethi-Nagy, Zsuzsanna; Abraham, Edit; Fabri-Ordogh, Lilla; Csonka, Akos; Vilmos, Peter; Debski, Janusz; Dadlez, Michal; Glover, David M.; Lipinszki, Zoltan
Abstract : Abstract : Protein phosphatase 4 (PP4) is an evolutionarily conserved and essential Ser/Thr phosphatase that regulates cell division, development and DNA repair in eukaryotes. The major form of PP4, present from yeast to human, is the PP4c-R2-R3 heterotrimeric complex. The R3 subunit is responsible for substrate-recognition via its EVH1 domain. In typical EVH1 domains, conserved phenylalanine, tyrosine and tryptophan residues form the specific recognition site for their target's proline-rich sequences. Here, we identify novel binding partners of the EVH1 domain of the Drosophila R3 subunit, Falafel, and demonstrate that instead of binding to proline-rich sequences this EVH1 variant specifically recognizes atypical ligands, namely the FxxP and MxPP short linear consensus motifs. This interaction is dependent on an exclusively conserved leucine that replaces the phenylalanine invariant of all canonical EVH1 domains. We propose that the EVH1 domain of PP4 represents a new class of the EVH1 family that can accommodate low proline content sequences, such as the FxxP motif. Finally, our data implicate the conserved Smk-1 domain of Falafel in target-binding. These findings greatly enhance our understanding of the substrate-recognition mechanisms and function of PP4.